1988
DOI: 10.1193/1.1585497
|View full text |Cite
|
Sign up to set email alerts
|

The Mexico Earthquake of September 19, 1985—An Empirical Model to Predict Fourier Amplitude Spectra of Horizontal Ground Motion

Abstract: We analyze Fourier acceleration amplitude spectra of 14 coastal earthquakes (5.6 ≤ Ms ≤ 8.1) recorded at a hill zone site in Ciudad Universitaria (CU), Mexico City (282 ≤ R ≤ 466 km, R= closest distance from CU to the rupture area). The observed smoothed spectra are fitted to the following model log FS(T) = A(T) Ms + C(T) log(R) + B(T) where FS is the maximum spectral value of either of the two horizontal components at period T. The coefficients A, C, and B are obtained for 18 periods (2.5 ≥ T≥ 0.2 sec). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Several important issues, however, remained unresolved in the study of Singh et al (1988a). Because spectral ratios were studied, it was not possible to know which of the two earthquakes was anomalous in and near Mexico City, although the damage to the city and spectral regression of coastal earthquakes recorded in Ciudad Universitaria (CU), a hill-zone site in the city (Castro, Singh & Mena 1988), strongly suggested that the Michoacan earthquake was anomalous. Since the source displacement spectra were obtained by averaging the corrected spectra from stations at different azimuths and distances (Houston & Kanamori 1986a), any azimuthal variation of the anomalous ratio could not be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Several important issues, however, remained unresolved in the study of Singh et al (1988a). Because spectral ratios were studied, it was not possible to know which of the two earthquakes was anomalous in and near Mexico City, although the damage to the city and spectral regression of coastal earthquakes recorded in Ciudad Universitaria (CU), a hill-zone site in the city (Castro, Singh & Mena 1988), strongly suggested that the Michoacan earthquake was anomalous. Since the source displacement spectra were obtained by averaging the corrected spectra from stations at different azimuths and distances (Houston & Kanamori 1986a), any azimuthal variation of the anomalous ratio could not be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The earthquake was the second largest in Mexico during the 20th century (Singh et al 1988a). The amount of released energy was anomalously high (Singh et al ibid;Singh et al 1987;Castro et al 1988). The energy rose to twice its average value at frequencies near 0.5 Hz.…”
Section: The 1985 Earthquakementioning
confidence: 94%
“…The first attenuation law to estimate Fourier amplitude spectra at station CU, in the hill zone of Mexico City, was due to Castro et al [1988]. Ordaz et al [1994] improved the prediction using more data and a Bayesian regression approach: with the predicted Fourier amplitude spectra, the use of random vibration theory and an estimation of the duration of motion, it is possible to compute response spectra (Method 2).…”
Section: Computation Of Elastic Response Spectra At Hill Zone (Cu)mentioning
confidence: 99%